DENTAL MANAGEMENT AND OROFACIAL MANIFESTATIONS OF A PATIENT WITH ROBINOW SYNDROME* - Adil BAŞMAN; Gülsün AKAY; İlkay PEKER; Kahraman GÜNGÖR; Zühre AKARSLAN; Suat ÖZCAN; Cemile Özlem ÜÇOK (Istanbul University, 2017)
Robinow syndrome (RS) is an extremely rare condition. Characteristic craniofacial findings of RS include a fetal facial appearance, ear abnormalities and oral findings. The aim of this case report was to evaluate the oral findings of a 26-year-old man with RS and to describe the dental treatments performed. The patient had short stature, vertebral anomalies, short and broad fingers, a fetal facial appearance, gingival hyperplasia, fissured tongue, caries and multiple impacted teeth. Periodontal and restorative dental treatments were performed under aseptic conditions with due precautions. No surgical treatment was performed to the impacted teeth because of the lack of symptoms.